Two new species of Miltochrista from India (Lepidoptera, Erebidae, Arctiinae) - Joshi, Rahul; Singh, Navneet; Kirti, Jagbir Singh; Volynkin, Anton V.; Bucsek, Karol (Zootaxa, 2017)
Two new species, Miltochrista quadra Joshi, Singh & Volynkin, sp. nov. and Miltochrista pseudomodesta Joshi, Singh & Volynkin, sp. nov., of tribe Lithosiini (Erebidae: Arctiinae) are described from India. In addition, two species are restored from the synonymy and transferred to Miltochrista: Miltochrista rubricans (Leech, 1890), stat. & comb. nov. and Miltochrista szetschwanica (Daniel, 1952), stat. & comb. nov. Other new combinations are also proposed as Miltochrista aquila (Černý, 2009), comb. nov., Miltochrista discisigna (Moore, 1878), comb. nov., Miltochrista weidenhofferi (Černý, 2012), comb. nov., Miltochrista unipuncta (Leech, 1890), comb. nov., Miltochrista carnea (Poujade, 1886), comb.nov. and Miltochrista modesta (Leech, 1899), comb. nov.